Copper migration and surface oxidation of CuxBi2Se3 in ambient pressure environments. (1st October 2022) - Gross, Adam L; Falling, Lorenz; Staab, Matthew C; Montero, Metzli I; Ullah, Rahim R; Nisson, David M; Klavins, Peter; Koski, Kristie J; Curro, Nicholas J; Taufour, Valentin; Nemsak, Slavomir; Vishik, Inna M
Abstract: Chemical modifications such as intercalation can be used to modify surface properties or to further functionalize the surface states of topological insulators (TIs). Using ambient pressure x-ray photoelectron spectroscopy, we report copper migration in C u x B i 2 S e 3, which occurs on a timescale of hours to days after initial surface cleaving. The increase in near-surface copper proceeds along with the oxidation of the sample surface and large changes in the selenium content. These complex changes are further modeled with core-level spectroscopy simulations, which suggest a composition gradient near the surface which develops with oxygen exposure. Our results shed light on a new phenomenon that must be considered for intercalated TIs—and intercalated materials in general—that surface chemical composition can change when specimens are exposed to ambient conditions.